2021
DOI: 10.1021/acs.jpcc.1c06684
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Fragmentation below the Melting Point under Single Picosecond Laser Pulse Stimulation

Abstract: Understanding the laser−nanomaterial interactions that lead to nanomaterial fragmentation is important for nanoparticle manufacturing, energy, and biomedical sciences. So far, three mechanisms of laser-induced fragmentation have been recognized including non-thermal processes and thermomechanical force under femtosecond pulses and the phase transitions under nanosecond pulses. Here, we show that single picosecond (ps) laser pulse stimulation leads to an anomalous fragmentation of gold nanoparticles that deviat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…Moreover, our previous work demonstrated that under current experimental conditions, the plasmonic heating generated by the interactions between picosecond laser and AuNPs is not a key factor to be responsible for the BBB opening. 8,40 The above results are consistent with our in vivo investigation that showed increased BBB permeability via paracellular diffusion through the tight junctions.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our previous work demonstrated that under current experimental conditions, the plasmonic heating generated by the interactions between picosecond laser and AuNPs is not a key factor to be responsible for the BBB opening. 8,40 The above results are consistent with our in vivo investigation that showed increased BBB permeability via paracellular diffusion through the tight junctions.…”
Section: Discussionsupporting
confidence: 91%
“…Yet, in practice, experimental photoexcitation studies have reported vastly different efficiencies for heat deposition and related thermal threshold processes, such as particle melting or bubble formation . We have recently noticed that the transient lattice expansion, representing particle heating after picosecond laser excitation of gold nanospheres, or nanorods was found to be less than predicted by optical calculations, if the plasmon-resonant wavelength of 532 nm, respectively 800 nm (for rods), is used.…”
mentioning
confidence: 99%
“…14) However, the amount of heat dissipated from the particles is proportional to the surface area, that is, r 2 . 15,16) Therefore, the larger the radius of the particles, the higher the temperature reached by the pulse laser irradiation. Thus, the target was ablated more efficiently than opaque particles.…”
Section: Resultsmentioning
confidence: 99%